Brain Imaging and Ultrastructural Studies of the Effect of Electroacupuncture on Improving Learning and Memory Impairments in the Focal Cerebral Isch-emia Rats - Ruhui LIN; Kunqiang YU; Xiaojie LI; Congkuai ZHAO; Chunyan LI (康复学报)
Objective:To investigate the effect of electroacupuncture(EA)at Baihui and Shenting on the learning and memory ability in focal cerebral ischemia(MCAO)rats, and then explore the underlying mechanism.Methods:Forty-five male SPF(Specific Pathogen Free)rats were randomly divided into the sham operation control group(SC group), the ischemia model group(IC group)and the electroacupuncture group(EA group). A modified occlusion method was used to establish the middle cerebral artery occlusion(MCAO)focal cerebral ischemia-reperfusion (I/R) injury model in the IC group and the EA group. The rats were administered electroacupuncture at Baihui and Shenting for 7 days in the EA group. The learning and memory ability of the rats was evaluated by Morris water maze, the cerebral infarction volume was detected by the small animal MRI and TTC staining, the brain ultrastructure was observed by transmission electron microscopic (TEM).Results:The time finding the plat and the error rate significantly reduced in the EA group in comparison with that in the IC group, while the cerebral infarction volume significantly decreased and the brain ultrastructure(mitochondria, nuclear membrane, etc.)of the rats was improved significantly, which showed that there was a statistically significant difference between the groups(P<0.05).Conclusion:Electroacupuncture at Baihui and Shenting could improve the ability of learning and memory after MCAO by reducing the cerebral infarction volume and protecting the brain ultrastructure in rats.